Of diet and profit: on the question of subsistence crises in nineteenth-century Iran. Issue 2 (3rd March 2016) - Kazemi, Ranin
ABSTRACT: This article enquires into the socioeconomic causes of recurrent food scarcity in the nineteenth-century Middle East. Focusing on Iran as a case study, the paper shows that certain categories involved in the production and distribution of grain engaged in profiteering schemes and thereby contributed to the making of food shortage in urban settings. The most important of these groups were the government officials, the landed classes, and the grain merchants. The local bakers were also involved, but they did not have as decisive a role as the other groups. In showing how these categories engaged in market manipulation, the paper contends that food scarcity cannot be explained without a proper understanding of the commercialization of grain and the economic integration of the Middle East in the nineteenth century.